Impacts of the COVID-19 pandemic on vegetable production and countermeasures from an agricultural insurance perspective - Hai-ying GU; Chang-wei WANG (Journal of Integrative Agriculture, 2020)
In the face of the corona virus disease 2019 (COVID-19) pandemic, it is essential to stabilize the security of urban “shopping baskets”. Through a survey and interviews with 46 agricultural cooperatives in Shanghai, this paper analyzes the impact of the pandemic on vegetable production and offers suggestions on agricultural insurance. The research results show that: (1) the pandemic has impacted almost all stages of the vegetable supply chain but has had a greater impact on the sales stage; (2) the market risks of vegetable production have increased significantly, and the gap between the field price and the market price has widened. The sales price difference between traditional channels and e-commerce is notable; (3) farmers' incomes have generally declined due to the COVID-19 pandemic, and traditional small-scale farmers have suffered more losses; and (4) agricultural insurance plays an important role in stabilizing the supply of vegetables to the city. To minimize the impact of the pandemic on vegetable production and to stabilize both urban “shopping baskets” and farmers' incomes, it is necessary to further improve agricultural insurance, especially to provide insurance against market risks.